2020
DOI: 10.12965/jer.2040366.183
|View full text |Cite
|
Sign up to set email alerts
|

Effects of swimming exercise on social isolation-induced memory impairment and apoptosis in old rats

Abstract: Effect of swimming exercise on serotonin (5-hydroxytryptamine, 5-HT) expression and apoptosis in social isolation rats during old age was investigated. Rats in the old social isolation groups were housed alone per cage for 4 weeks. Rats in the swimming exercise groups were allowed to swim for 30 min once daily for 4 weeks. Morris water maze task determined spatial working memory and elevated plus maze test determined anxiety. Immunohistochemistry for tryptophan hydroxylase (TPH) and 5-HT in the dorsal raphe an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 25 publications
3
30
0
Order By: Relevance
“…Cleaved caspase-3 expression and Bax to Bcl-2 ratio were increased by CCl 4 treatment, showing that CCl 4 initiated apoptosis ( Ko et al, 2020 ). In social isolation old rats, swimming inhibited Bax expression and enhanced Bcl-2 expression, indicating that apoptosis was supressed ( Park et al, 2020 ). Voluntary wheel running suppressed cleaved caspase-3 expression with Bax expression and enhanced Bcl-2 expression in the hippocampus of the brain inflammation rats ( Ko and Ko, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cleaved caspase-3 expression and Bax to Bcl-2 ratio were increased by CCl 4 treatment, showing that CCl 4 initiated apoptosis ( Ko et al, 2020 ). In social isolation old rats, swimming inhibited Bax expression and enhanced Bcl-2 expression, indicating that apoptosis was supressed ( Park et al, 2020 ). Voluntary wheel running suppressed cleaved caspase-3 expression with Bax expression and enhanced Bcl-2 expression in the hippocampus of the brain inflammation rats ( Ko and Ko, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…TUNEL staining is used to detect DNA fragmentation, which is characteristics of apoptosis. Social isolation in old rats increased TUNEL-positive cell number, indicating that social isolation promoted apoptosis (Park et al, 2020b). The Ki67 protein is present during all active stages of the cell cycle, such as G1, S, G2, and mitosis, but not in resting cells (G0).…”
Section: Introductionmentioning
confidence: 95%
“…Tryptophan hydroxylase positive cell, 5-hydroxytryptamine positive cells, and Bcl-2 (B-cell lymphoma 2) expression have increased while BAX (Bcl-2-associated X protein) and cytochrome c expression were suppressed while swimming exercise. It was shown that swimming would lead to apoptosis prevention, reduced anxiety, and enhancement in social and learning capability in rats (114).…”
Section: Non-drug Treatmentsmentioning
confidence: 99%